The Criminalization of Black Children: Race, Gender, and Delinquency in Chicago's Juvenile Justice System, 1899-1945 - Agyepong, Tera Eva (Justice, Power, and Politics Ser, 2018)
Cover -- Contents -- Acknowledgments -- Introduction. Contingent Childhood: Black Children and the Making of Juvenile Justice -- Chapter One. Race-ing Innocence: The Emergence of Juvenile Justice and the Making of Black Delinquency -- Chapter Two. Boundaries of Innocence: Race, the Emergence of Cook County Juvenile Court, and Punitive Transitions -- Chapter Three. Constructing a Black Female Delinquent: Race, Gender, and the Criminalization of African American Girls at the Illinois Training School for Girls at Geneva -- Chapter Four. Flight, Fright, and Freedom: Delinquency and the Construction of Black Masculinity at the Training School for Boys at St. Charles -- Epilogue -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y